Stage IV Small Lymphocytic Lymphoma Presenting with Unilateral Vision Loss. (11th January 2020) - Le, Christopher; Jacob, Adam; Iyengar, Devarajan; Dedousis, John; Tsompanidis, Antonios
Abstract : Small lymphocytic lymphoma (SLL) is a manifestation of chronic lymphocytic leukemia (CLL) in which malignant B-cell lymphocytes accumulate in the lymph nodes or bone marrow. In this report, we describe the medical course of a patient diagnosed with stage IV small cell lymphocytic lymphoma, who presented to the emergency room with acute neurologic manifestations of SLL.